2002
DOI: 10.1210/en.2002-220506
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Augments Voltage-Gated Ca2+ Currents and Synergistically Increases Growth Hormone (GH) Secretion with GH-Releasing Hormone in Primary Cultured Ovine Somatotropes

Abstract: Orexins are recently discovered neuropeptides that play an important role in the regulation of hormone secretion, and their receptors have been recently demonstrated in the pituitary. The effects of orexin-A on voltage-gated Ca2+ currents and GH release in primary cultured ovine somatotropes were examined. The expression of orexin-1 receptor was demonstrated by RT-PCR in ovine somatotropes, from which Ca2+ currents were also isolated as L, T, and N currents. Application of orexin-A (100 nM) significantly and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 60 publications
(79 reference statements)
4
27
2
4
Order By: Relevance
“…The fact that OX-A failed to modify in vitro GH secretion suggests that its inhibitory effect was taking place at the hypothalamic level. This is in contrast to previous data obtained in porcine somatotrophs where it was found that OX increased in vitro GH responses to GHRH (16). It is likely that these discrepancies reflect interspecies differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fact that OX-A failed to modify in vitro GH secretion suggests that its inhibitory effect was taking place at the hypothalamic level. This is in contrast to previous data obtained in porcine somatotrophs where it was found that OX increased in vitro GH responses to GHRH (16). It is likely that these discrepancies reflect interspecies differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, we also assessed the effect of OX-A on in vitro GH secretion, since the presence of OX receptors in the human anterior pituitary has been recently reported (10), as well as the activation of voltage-gated Ca 2þ currents in porcine somatotrophs (16).…”
Section: Introductionmentioning
confidence: 99%
“…van den found that the same inhibitor of PKC that we used totally blocked the [Ca 2ϩ ] i increase. In several other studies, PKC has been suggested to be a crucial intermediate effector in orexin action, often with downstream effects linked to specific ion channels (Uramura et al, 2001;Xu et al, 2002;Kohlmeier et al, 2004) or less well defined ion conductances (Yang et al, 2003). PKC has long been known to modulate VGCCs (Yang and Tsien, 1993) and K ϩ conductances (Henry et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reproduction, ORX neurons project to the PeVN adjacent to somatostatin neurons , suggesting a possible role in regulating GH. Indeed, ORX A and B receptors are expressed in somatotropes and both molecules activate calcium channels in the pituitary via protein kinase C mechanisms (Xu et al, 2002 and. ORX B will also release GH from isolated pituitary cells.…”
Section: Introductionmentioning
confidence: 99%